Study guides

☆☆

Q: -6x plus 72 equals x

Write your answer...

Submit

Still have questions?

Related questions

6x + 10 = 72 6x = 72 - 10 x = 62/6 x = 10.3333

x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)

2x2+6x-8 = 72 2x2+6x-8-72 = 0 2x2+6x-80 = 0 (2x-10)(x+8) = 0

6x+x = 7x

x2 + 6x - 72 = (x + 12)(x - 6)

(x + 12)(x - 6) = 0 x = 6 or -12

6x

5x + x - 6x + 2x = 2x

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

-6x

x=10

If: 9x+7 = 6x+25 Then: x = 6

x=-3

If: x-9 = 6x+7 then x works out as -3.2

6x+4=52 6x=48 x=8

Using the quadratic equation formula the value of x is -8 or 5

6x+4 = x+12+4x-6 6x-x-4x = 12-6-4 x = 2

x=3 becaus: 6x=x+15 5x=15 (-x) x=3 (divided by 5)

6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.

X equals to 8

x=5

20

x = -3

-324

x = -1